Relevansi Antara Kafa’ah dalam Pernikahan dengan Tujuan Pendidikan Islam - Istibsjaroh Istibsjaroh; Luluk Lailatul Mufarida; Qurrotul Ainiyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
Kafa'ah (balance / equality) in choosing a mate aims to realize the goals of the family are sakinah, mawaddah and rahmah and blessed with children who are salih and salihah. The only reason hat is considered is religion, because parents are educators who will later be responsible for implementing family education towards the realization of the marriage goal. This research examines the concept of marriage kafa'ah and its relevance to the concept of Islamic education. This study uses a type of literature with an analytical descriptive approach that will be analyzed with content analysis. This study resulted in a conclusion that Kafa'ah religion (aqeedah,worship, morality) was the only kufu that became a consideration to realize the purpose of marriage. The relevance of kafa'ah in Islamic education is very important, because parents are the primary educators who should have strong Islamic religious competencies, the material comes from Allah, with the correct method and is supported by an Islamic environment, the educational goals will be easily realized, so that born children who are salih and salihah.